From residency for creation Toning the sensitive body: epistolary dialogue between Vitor Lemos and Tiago Porteiro (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In September 2021, in Lisbon, took place the International Artist Residency guided by Carlos Simioni (Lume Teatro/Campinas) and Stephane Brodt (Amok Teatro/Rio de Janeiro), Toning the sensitive body. The pedagogues-researchers-artists Tiago Porteiro and Vitor Lemos were part of it. The first carried out the proposed practices and the second observed them. It was from this different positioning that the authors jointly developed a reflection in epistolary format. In the letters, notions of sensitive body and its implications in the processes of formation are discussed, as well as considerations about methodologies of research-creation of the actor-actress. At the end of the conversation the theme of "(un)education" appears through a more direct dialogue, associating it to themes disseminated throughout the letters.
Keywords: Residency; Body; Performance art; Epistolary dialogue; Actor/actress creation processes